Efeitos cardiovasculares induzidos por um novo doador de óxido nítrico, o nitrato tetrahidrofurfurílico (NTHF), em ratos - Furtado, Fabiola Fialho (2014)
Previous studies have show that the organic nitrate tetrahydrofurfuryl (NTHF) induces vasorelaxation in mesenteric artery rings with involvement of the NO-sGC-PKG pathway. This study evaluated the action of NTHF on cardiovascular parameters in spontaneously hypertensive (SHR) and Wistar Kyoto (WKY) rats, investigating: the nitric oxide (NO) release, acute toxicity, the NTHF effect on blood pressure and heart rate, its vasorelaxant effect and its ability to induce tolerance. NTHF increased NO levels in rat aortic smooth muscle cells (SMC) and cardiomyocites. In acute toxicity studies, a high single dose from NTHF showed low toxicity. In normotensive animals, NTHF induced hypotension after oral administration of NTHF, and bradycardic and hypotensive effects following administration of this nitrate. These results were similar that found using nitroglycerine (NTG). In addition, these effects were not altered by pretreatment with hexamethonium, a ganglionic blocker. However the treatment with methylene blue, a sGC inhibitor, promoted attenuation of both hypotensive and bradycardic effects, suggesting the involvement of the sGC pathway in these effects. In mesenteric artery rings from SHR and WKY rats precontracted with phenylephrine, NTHF induced concentration dependent vasodilatation in both intact and removed endothelium. This result suggests that the vasorelaxant effect is an endothelium derived relaxation factors (EDRFs) independent mechanism. Furthermore, in the presence of NO° scavenging (PTIO) or ODQ, a sGC inhibitor, the vasorelaxation induced by NTHF was decreased, indicating the involvement of NO-sGC pathway in this response in both SHR and WKY. In the presence of cyanamide, an aldehyde dehydrogenase (mtALDH) inhibitor, the vasorelaxant effect was diminished, suggesting that NTHF is metabolized by this enzyme. After exposure to depolarizing agent KCl, the nitrate effect was significantly attenuated, a characteristic of substances which acts by K+ channels activation. This effect was confirmed after using tetraetylamonium (TEA), a K+ channels inhibitor. In normotensive rats treated with NTHF, the acute administration of NTHF promoted bradycardia and hypotension were are not changed in relation to which those observed in vehicle-treated animals, suggesting that organic nitrate did not induce in vivo tolerance. In vitro tolerance was evaluated in both mesenteric artery rings from animals pretreated with NTHF as well as rings previously exposed to isolated concentrations of NTHF. The vasorelaxant effect was not modified by pretreatment or exposure to NTHF, unlike that observed with NTG. In rings treated with NTG, the effect induced by NTHF was not modified, indicating that NTHF did not promote in vitro tolerance. The results demonstrated that NTHF promoted hypotensive and bradycardic effects in both SHR and WKY rats, with involvement of sGC enzyme; NTHF induced a vasorelaxant effect with participation of NO-sGC-PKG pathway and K+ channels. These effects seem to be mediated by NO release from cardiomyocites and SMC. Finally this study will help to advance the field towards clinical trials, since NTHF caused low toxicity and this nitrate was devoid of in vivo and in vitro tolerance.